Integrating mathematics with culture: Implementation of a hypothetical learning trajectory using traditional lapik pandan from Koto Dian - Arshinta Vrasetya; Noperta (Journal Focus Action of Research Mathematic (Factor M), 2026)
Mathematics learning in elementary schools is often considered abstract, making it difficult for students to relate concepts to real-life contexts. Previous studies have shown a lack of integration of local cultural contexts in geometry learning, resulting in a gap in learning strategies that help students understand mathematical concepts in a meaningful way. This study aims to implement the Hypothetical Learning Trajectory (HLT) with the context of pandan weaving, which is the local wisdom of Koto Dian Village, in the material on the area and perimeter of squares. The research subjects were 28 sixth-grade students at a state primary school in Sungai Liuk, Jambi. HLT was applied through three stages, and data were collected through observation and interview techniques, using validated research instruments in the form of Student Worksheets (LKPD), observation guidelines, and interview guidelines, and analyzed descriptively and qualitatively. The results of the study show that the local cultural context can improve students' ability to recognize square shapes, calculate perimeter and area, and apply this knowledge in everyday life. Students also showed active engagement, a high level of curiosity, and development of mathematical thinking skills, including abstraction, generalization, and selection of appropriate problem-solving strategies. These findings indicate that the integration of Realistic Mathematics Education (RME) based on local culture supports meaningful and cognitively challenging learning. Therefore, learning media based on local wisdom is recommended as an effective strategy for improving mathematics understanding in elementary schools.